Prediction of stroke in patients with severe aortic stenosis by left atrial appendage filling defect patterns on early and late-phase computed tomography - Pietro G. Lacaita; Sven Bleckwenn; Fabian Barbieri; Yannick Scharll; Johannes Deeg; Nikolaos Bonaros; Gerlig Widmann; Gudrun M. Feuchtner (International Journal of Cardiology: Heart & Vasculature)
Background: Stroke is a feared complication after TAVI. The objective was to assess whether left atrial appendage (LAA) filling-defect (FD) patterns from early and late-phase computed tomography (CT), predict stroke/TIA in patients with severe aortic stenosis. Methods: 124 patients with severe aortic stenosis (79.5y, 46.8% females) who underwent CT-Angiography for TAVI-planning were included (66.1% underwent TAVI, 18.6% surgical, 15.3% conservative treatment).CT-image-analysis included: CT-density (HU) from LAA tip-to-base and HU-gradients (I-III), the HU-ratio LAA/aorta, left-atrial-wall-thickness (LAWT) and the periatrial fat attenuation index (FAI). Results: Stroke/TIA rate was 9.6 %. LAA-HU-gradient was slightly higher in non-stroke patients (p = 0.087). Persisting FDs during the late-phase were associated with stroke (p = 0.047) but not early-phase FDs. Early-phase FDs with HU < 245 (n = 15) were correlated with stroke (p = 0.05). A LAA-HU-gradient > 10HU had 91 % sensitivity and 68 % specificity for prediction of stroke. LAA-HU gradient I had a moderate accuracy (c = 0.592; 95 %CI:0.472–0.711; p = 0.317) for discrimination of stroke during the early phase, which enhanced during the late phase (c = 0.686;95 %CI:0.503–0.868; p = 0.046). Patients with stroke had a higher rate of FDs with HU-progression from early to late phase (>10HU)(p = 0.013), while the ratios LAA/aorta, LAWT, and periatrial-FAI were not different. Among clinical parameters, only age predicted stroke but not CHA2DS2-VASc-score. In multivariate analysis, late-phase FDs (p = 0.059)(OR 5.66: 95 %CI:0.936–34.28) but not early-phase FD were associated with stroke, and none of the major conventional risk factors. Conclusion: Persisting LAA-filling defects on CT during the late-phase, and early-phase FD with <245HU predict stroke, and a CT-density progression >10HU from early-to-late phase. LAA-FD may improve stroke risk stratification.